The frustration of being odd: universal area law violation in local systems. (27th August 2019) - Giampaolo, Salvatore Marco; Ramos, Flavia Brága; Franchini, Fabio
Abstract: At the core of every frustrated system, one can identify the existence of frustrated rings that are usually interpreted in terms of single–particle physics. We check this point of view through a careful analysis of the entanglement entropy of both models that admit an exact single–particle decomposition of their Hilbert space due to integrability and those for which the latter is supposed to hold only as a low energy approximation. In particular, we study generic spin chains made by an odd number of sites with short-range antiferromagnetic interactions and periodic boundary conditions, thus characterized by a weak, i.e. nonextensive, frustration. While for distances of the order of the correlation length the phenomenology of these chains is similar to that of the non-frustrated cases, we find that correlation functions involving a number of sites scaling like the system size follow different rules. We quantify the long-range correlations through the von Neumann entanglement entropy, finding that indeed it violates the area law, while not diverging with the system size. This behavior is well fitted by a universal law that we derive from the conjectured single–particle picture.